Probiotic reduces vaginal HPV abundance, improves immunity and quality of life in HPV-positive women : a randomised, placebo-controlled and double-blind study - Xu, P.; Mageswary, U.; Nisaa, A. A.; Balasubramaniam, S. D.; Samsudin, S. B.; Rusdi, N.I.B.M; Jerip, A.R.A; Oon, C.E; Bakar, M.H.A; Rajendran, D.; Tan, J. J.; Roslan, F. F.; et al. (Wageningen Academic, BRILL, 2025)
The Human Papillomavirus (HPV) is one of the main causes of cervical cancer in women, while there are currently no treatment nor intervention to reduce the concentration of cervical HPV. We thus aimed to investigate the effects of a probiotic Lactiplantibacillus plantarum Probio87 (orally administered at 9 log CFU/day) or placebo for 12-weeks, on reducing the abundance of vaginal HPV in HPV-positive women. A parallel, randomised, double-blind and placebo-controlled study was performed where women were randomised to either the probiotic (n = 44, mean age 41.70 ± 1.06 years) or placebo (n = 45, mean age 41.13 ± 1.20 years). After 12 weeks, the probiotic group showed reduced vaginal HPV abundance (P=0.001) and Nugent scores (P<0.001) as compared to the placebo. VAS and VuAS questionnaires showed that the probiotic group had improved vulvar dryness (P=0.023), soreness (P=0.049), social interactions, daily activities (P<0.05), and sexual activity (P=0.022) compared to the placebo group. Blood gene expressions showed that the placebo group had higher upregulation of pro-inflammatory cytokines (IL-1β, P=0.006; IFN-γ, P=0.028) and T-cell markers (CD44, P=0.008; CXCR5, P=0.040; CD4, P=0.016) compared to the placebo group, indicating increased inflammation. Neurotrophic factors BDNF and CREB were upregulated in the placebo group (P<0.05), with higher IDO (P=0.001) and TDO (P=0.036) expressions compared to the probiotic group, suggesting increased kynurenine pathway activity and stress. Overall, probiotic supplementation appeared to reduce the abundance of vaginal HPV, possibly by lowering inflammation and enhancing immunity while mitigating the negative impacts of HPV infection on quality of life in HPV-positive women.